Cobalt(III)-Catalyzed C–H Activation/Annulation Cascade Reaction of N-Chlorobenzamides with 2-Acetylenic Ketones at Room Temperature - Wu, Zhouping; Zheng, Qinwen; Lv, Guanghui; Lai, Ruizhi; Hu, Yao; Hai, Li; Wu, Yong (Synthesis, 2022)
A mild cascade annulation of Co(III)-catalyzed N-chlorobenzamides with 2-acetylenic ketones at room temperature is reported. This reaction sets N–Cl bond of N-chlorobenzamide as an internal oxidant, displaying broad functional group tolerance and excellent reverse selectivity of alkyne insertion under mild and safe conditions. The cascade reaction offers a straightforward and mild protocol to construct isoquinolones in high yields at room temperature.
Keywords: C–H activation; cobalt; N-chlorobenzamide; annulation; room temperature